“Narrating” Bodies. Physical “Reflexive” Activities between Gender Images and Socio-pedagogical Processes - Research on the Yoga’s Representations - Russo, Giovanna; Rossetti, Francesca (Central European Journal of Educational Research, 2022)
This article intends to offer a reflection on how reflexive physical activities can support a socio-pedagogical approach to educating about gender diversity through media communication. We use the term “reflexive” to refer to all those activities aimed at enhancing the person and his relationships, self-realization, selfknowledge, and self-improvement: in other terms, a circuit of bodily experiences that determine bodily knowledge as a social construction (as described by Connel, 2005). These activities focus mainly on ethical purposes, rather than on performative ones. An example of such disciplines can be considered the practice of yoga which is a currently growing phenomenon both in Europe and in the United States. Yoga is practiced today in the USA by 35.2 million adults, by over 2.5 million people in Italy, and is garnering scientific interest in its contributions to balanced, healthy growth of children and adults. The World Health Organization, in its global action plan on physical activity 2018-2030: More Active People for a Healthier World, calls it a means to improve health. The diffusion of these disciplines responds to a personal and social search for meaning that weighs especially heavily on highly secularized Western culture. This diffusion also portrays a media phenomenon, whose images and messages validate and reinforce capitalist ethics. From this point of view, the “mediated” representation of sports bodies appears to apply to the world of consumers. The images of women practicing yoga, oriented toward alternative values rather than beauty and sexuality, are above all confirmed by the purchase of goods and services that are not related to outward personal appearance. Using the results of an analysis carried out in 2021 of two main international yoga magazines, we are going to discuss the role of yoga as a “reflexive” physical activity and its pedagogical potential oriented to the body as a “primary place of experience”, not just a consumer item, but also a tool for education about gender diversity.